1991
DOI: 10.1007/bf00571925
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mutations that occurred on the genome of Japanese encephalitis virus during the attenuation process

Abstract: The total nucleotide sequences of the genomes of two Japanese encephalitis virus (JEV) strains, the attenuated vaccine strain SA14-14-2 and its parental virulent strain SA14, were determined by using the molecular cloning technique. The sequence analysis revealed that both virion RNA molecules were 10,976 nucleotides long with 95 and 585 flanking bases at the 5' and 3' untranslated sequences, respectively. A single, long open reading frame spanning 10,296 nucleotides was observed to encode a polyprotein of 343… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 22 publications
0
52
0
Order By: Relevance
“…18 In addition, several laboratories have sequenced the JEV SA14-14-2 vaccine strain over the last 20 years with significantly different results 27,28,48 (Table 2), suggesting that the vaccine seed virus is not clonal, and this could affect attenuation and immunogenicity between vaccine lots. It was for these reasons that we initiated the development of a second-generation, recombinant JEV SA14-14-2 live-attenuated vaccine produced in WHO qualified Vero cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In addition, several laboratories have sequenced the JEV SA14-14-2 vaccine strain over the last 20 years with significantly different results 27,28,48 (Table 2), suggesting that the vaccine seed virus is not clonal, and this could affect attenuation and immunogenicity between vaccine lots. It was for these reasons that we initiated the development of a second-generation, recombinant JEV SA14-14-2 live-attenuated vaccine produced in WHO qualified Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…The JEV SA14 underwent 100 passages in primary hamster kidney (PHK) cells, several plaque purifications in primary chick embryo cells, peripheral passages in Syrian hamsters, and suckling mice, followed by additional plaque purifications in PHK cells, which resulted in the accumulation of attenuating mutations found in the JEV SA14-14-2 genome. [27][28][29][30] There appear to be multiple attenuating mutations in the JEV SA14-14-2 E protein, 31 however E-E138K seems to be particularly important. [31][32][33][34][35] Interestingly, a recombinant WT JEV Nakayama virus bearing the 5 UTR, C, prM, and E genes of JEV SA14-14-2 had residual neurovirulence in mice, indicating that mutations located outside the structural protein genes might also contribute to attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular basis of JE virus attenuation has not been elucidated, although the entire genomes of both virulent parent SA14 and attenuated vaccine clones, SA14-14-2/PHK (Aihara et al, 1991) and SA14-14-2/ PDK (Nitayaphan et al, 1990), have been sequenced and compared. Nucleotide sequences of SA14 published by the two groups are not identical, and nucleotide differences were identified throughout the genome between parent and the two attenuated viruses.…”
mentioning
confidence: 99%
“…A new inactivated vaccine licensed in US, Europe and Australia is also prepared from SA14-14-2 grown in Vero cells and is called . Another important vaccine is the live attenuated SA14-14-2 vaccine, which is derived via extensive passage series in primary hamster kidney ce l ls, fol lowed b y UV irradiat i on, plaque purification and passage in hamsters and suckling mice (Ni et al, 1994;Aihara et al, 1991). SA14-14-2 was licensed in china in 1988 and provides 80-96% protection after a single dose and further studies in China have shown 97.5% efficacy after 2 doses 1 year apart (Tandan et al, 2007;Hennessy et al, 1996;Xin et al, 1988).…”
Section: Vaccines and Viral Inhibitorsmentioning
confidence: 99%